Description Of The Relationship Between Language And Thought (The Review of Diabetic Studies, 2025)
Language has existed for thousands of years, and for many centuries, man has been in awe of this creation, a wonder and a wonder. Language, in particular, the problems of whether it is a divine or artistic language, seriously attracted the attention of the first intelligent people who, although in primitive times, tried to understand the essence and laws of various phenomena in nature and society.